2019
DOI: 10.1007/s00426-019-01145-x
|View full text |Cite
|
Sign up to set email alerts
|

Lifting cognition: a meta-analysis of effects of resistance exercise on cognition

Abstract: The health benefits of resistance exercises are well established, however the effects of resistance training on cognition are not as well understood. The purpose of this meta-analysis was to evaluate the evidence of resistance exercise's effects on cognition. A systematic search identified 21 studies that were included in the analyses. These articles ranged in the protocols utilized and in how they studied the effects of resistance training on cognition. Four primary analyses were carried out to assess the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 99 publications
8
73
0
1
Order By: Relevance
“…For example, Esteban-Cornejo et al (2017) consider that it is necessary to assess how the interaction of different physical qualities could modulate the brain development. Landrigan et al (2019) performed a metaanalysis and observed the effects of strength training on cognitive functioning, highlighting the importance in the development of this physical quality. These authors consider that both the cognitive demands of the exercise itself and other physiological effects derived from physical exertion would explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Esteban-Cornejo et al (2017) consider that it is necessary to assess how the interaction of different physical qualities could modulate the brain development. Landrigan et al (2019) performed a metaanalysis and observed the effects of strength training on cognitive functioning, highlighting the importance in the development of this physical quality. These authors consider that both the cognitive demands of the exercise itself and other physiological effects derived from physical exertion would explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…For example, physical training generates cognitive demands that have an impact on the brain. In addition, physiological processes are implemented as increased levels of neurotrophic or hormonal factors that facilitate brain plasticity processes (Landrigan et al, 2019). These analyses have shown that there are differences among boys and girls in the level of correlation and in the predictive capacity of the variables.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence in the literature that acute resistance exercises and long-term resistance training improve cognitive functions [1][2][3][4]. However, the underlying mechanisms for these cognitive improvements are not fully understood yet, although they seem to rely on changes at multiple levels [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanisms for these cognitive improvements are not fully understood yet, although they seem to rely on changes at multiple levels [5][6][7]. One assumption is that resistance exercises may act as an 'indirect' form of cognitive training since for their execution subjects need to constantly engage cognitive resources as they have to pay attention to perform the movement with an appropriate technique (e.g., squat), to produce an appropriate level of force, and to observe the surroundings in order not to harm themselves or others [3]. Engaging specific cognitive resources to execute a specific motor task (e.g., resistance exercise such as squatting) is deemed a necessary prerequisite to guide the facilitation effects of physical exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on acute aerobic exercise and its priming effects on cognitive function, learning, and motor skill acquisition. For review papers on the benefits of aerobic, resistance, and combined aerobic and resistance exercise on cognitive performance, please see the reviews of Brunt et al (2019), Landrigan et al (2019), Smith et al (2010), Wilke et al (2019), and Zheng et al (2016).…”
Section: Introductionmentioning
confidence: 99%